Silver Empowerment Fostering Strengths and Connections for an Age-Friendly Society - De Witte, Jasper; Van Regenmortel, Tine (Leuven University Press, 2023)
The strengths and opportunities of ageing and the ageing population. Silver empowerment is a valuable paradigm to improve care and support systems for older persons. It aims to counteract the dominant image of ageing, which is all too often one of decline, dependency and vulnerability, and rather sees ageing and the ageing population as a challenge that opens up new opportunities. By focusing on the strengths and connections of older persons, silver empowerment strives for an inclusive, age-friendly society that will allow everyone to grow old with dignity and meaning. In this book, leading academics from a variety of disciplines discuss ways to enhance the empowerment of older persons in practice. Covering a wide range of topics such as resilience, loneliness, community-based care, the interplay between formal and informal care, the inclusion of older persons' perspectives in research and care, and empowering policy, Silver Empowerment is of interest to academics, policy makers and practitioners interested in empowerment and care and support systems for older persons.